Racial and Ethnic Disparities in Maternal Outcomes and the Disadvantage of Peripartum Black Women: A Multistate Analysis, 2007–2014 - Tangel, Virginia; White, Robert S.; Nachamie, Anna S.; Pick, Jeremy S. (American Journal of Perinatology, 2019)
Objective Racial and ethnic disparities in obstetric care and delivery outcomes have shown that black women experience high rates of pregnancy-related mortality and morbidity, along with high rates of cesarean delivery, compared with other racial and ethnic groups. We aimed to quantify these disparities and test the effects of race/ethnicity in stratified statistical models by insurance payer and socioeconomic status, adjusting for comorbidities specific to an obstetric population.Study Design We analyzed maternal outcomes in a sample of 6,872,588 delivery records from California, Florida, Kentucky, Maryland, and New York from 2007 to 2014 from the State Inpatient Databases, Healthcare Cost and Utilization Project. We compared present-on-admission characteristics of parturients by race/ethnicity, and estimated logistic regression and generalized linear models to assess outcomes of in-hospital mortality, cesarean delivery, and length of stay.Results Compared with white women, black women were more likely to die in-hospital (odds ratio [OR]: 1.90, 95% confidence interval [CI]: 1.47–2.45) and have a longer average length of stay (incidence rate ratio: 1.10, 95% CI: 1.09–1.10). Black women also were more likely to have a cesarean delivery (OR: 1.12, 95% CI 1.12–1.13) than white women. These results largely held in stratified analyses.Conclusion In most insurance payers and socioeconomic strata, race/ethnicity alone is a factor that predicts parturient outcomes.
Keywords: racial/ethnic disparities; in-hospital maternal mortality; cesarean delivery; administrative database; outcomes research; maternal length of stay